Architecture of the climate fight - Lobovikov Maxim; Zinovyeva Irina; Pryadilina Natalia (BIO Web of Conferences)
Global warming is a serious challenge to the world’s population. Scientists are still arguing about the causes, speed and possible threats of the climate change and ways to combat them. Meanwhile, the planetary climate is changing not for the better. Warming causes global environmental, economic, social and political problems and disasters. Further changes threaten the quality of life and the very lives of people on the planet Earth. Over the four decades a global mechanism of legal, policy and market instruments, was designed to revert climate change. The mechanism is to stabilize and reduce GHGs in the atmosphere by reducing their emissions and absorbing them in long-term sinks above and under the ground. The architecture and dynamics of this mechanism and the interaction of its individual parts and elements are the subject of this article.